GOALS AND OBJECTIVES OF INCLUSIVE EDUCATION (Eureka Journal of Language, Culture & Social Change, 2026)
This paper provides a comprehensive analysis of the concepts, core goals, and operational objectives of inclusive education. It underscores the critical importance of providing equitable educational opportunities for all children, specifically focusing on those with disabilities and diverse special educational needs (SEN). The paper traces the historical evolutionary trajectory of inclusive education, mapping the shift from institutional isolation to modern inclusive practices through foundational concepts such as deinstitutionalization, normalization, integration, and mainstreaming. Furthermore, it examines the structural role of inclusive education in building a democratic, empathetic, and supportive society. It highlights the systemic changes required in school infrastructure, curriculum design, and teacher training to ensure that every learner can actively participate, feel a sense of belonging, and develop their full potential.
Keywords: Inclusive education, special needs education, integration, mainstreaming, normalization, deinstitutionalization, equal opportunities, disabilities, social inclusion, educational support, Universal Design for Learning.